Communicating death with humor: Humor types and functions in death over dinner conversations. Issue 4 (21st April 2022) - Lambert South, Andrea; Elton, Jessica; Lietzenmayer, Alison M.
Abstract: Using Death over Dinner conversations, we examined 83 family and/or friend groups comprising 424 participants to understand how humor is used when talking about death and dying. Thematic analysis revealed that family and friends used six types of humor in their conversations about death: entertainment humor, gallows humor, tension-relieving humor, confused/awkward laughter, group humor/narrative chaining, and self-deprecating humor. We discuss the benefits and drawbacks of the use of humor when discussing uncomfortable topics, practical applications related to humor and death, as well as possibilities for future research.